Solvation of NaPF6 in Diglyme Solution for Battery Electrolytes. Issue 12 (4th September 2020) - Jensen, Anders C. S.; Au, Heather; Gärtner, Sabrina; Titirici, Maria‐Magdalena; Drew, Alan J.
Abstract: Glymes present a promising new group of electrolyte solvents for sodium‐ion batteries. Not only do they have excellent electrolyte solvent properties but they also enable the intercalation of sodium into graphite as sodium‐glyme complexes, a reaction which is not possible for sodium in conventional electrolyte solvents. However, little is known about the solution structure of these complexes, especially for sodium salts, and why glymes enable this process while other commonly used electrolyte solvents do not. Here, a combination of neutron total scattering and empirical potential structure refinement was used to characterize the solvent structure around the ions, for a NaPF6 solution in diglyme. This showed that 82 % of the sodium ions are bound as Na + (diglyme)2 complexes, the conformation needed for intercalation into graphite, with the rest forming various contact ion pairs. The model also showed that very weak hydrogen bonding interactions exist between the anion and the diglyme molecules. Abstract : The art of solvation : Diglyme is a promising electrolyte for sodium‐ion batteries technology and have shown good performance and low SEI formation with carbon anodes. Using total neutron scattering, the local structure of the sodium in diglyme is observed and the diglyme molecules are found to physically separate the sodium cation from the anion by forming a Na + (diglyme)2 − complexes, suggesting that these complexes may be the underlying reason for their high performance.